Beyond zero: Activating triple zero airports - Cooke, Erin; Bernheim, Anthony (Journal of airport management, 2022)
San Francisco International Airport (SFO) was the first airport to adopt a triple zero goal — zero energy, zero carbon and zero waste — in 2016. Five years in, this ambition is actively being implemented by subject matter expert ambassadors across campus. Airport staff and partners have co-created delivery plans, operationalised strategies and reported results on activating net zero and decarbonised buildings, doubling onsite renewables, procuring all-electric shuttle buses and light-duty vehicles, delivering sustainable aviation fuel to all aircraft, eliminating single-use plastics and so many more ‘zero’ gains. SFO staff have taken up the mantle by introducing new ideas and approaches, as well as seeking out a variety of thirdparty certifications to demonstrate our continued commitment to the health of our planet, passengers and employees. This is just the beginning. The path to zero is high-impact, highly collaborative work that requires the partnership of our design and construction teams, airlines, business partners, individuals and, most importantly, a global network of airports who have the aspiration AND passion for new and unexpected ways of incorporating sustainability into the way we work, how we develop our facilities and how we operate as our direct means to abate the climate crisis. Outlined herein is SFO’s path to zero, with the intention of defining a joint roadmap for airport partners to team up to ensure we each serve an active role in supporting the health of our communities, workforce and shared, but threatened, planet.